2013
DOI: 10.1007/s11060-013-1120-8
|View full text |Cite
|
Sign up to set email alerts
|

Radionecrosis induced by stereotactic radiosurgery of brain metastases: results of surgery and outcome of disease

Abstract: Sterotactic radiosurgery (SRS) is an effective and commonly employed therapy for metastatic brain tumors. Among complication of this treatment, symptomatic focal cerebral radionecrosis (RN) occurs in 2-10 % of cases. The large diffusion of combined therapies as SRS followed by WBRT and/or CHT, has significantly amplified the number of patients who potentially might be affected by this pathology and neurosurgeons are increasingly called to treat suspected area of RN. Results of surgery of RN in patients with br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(42 citation statements)
references
References 48 publications
0
40
0
2
Order By: Relevance
“…At doses of 16-22 Gy given in a single fraction, RN may develop in up to 68 % of treated lesions, depending on several patient-related and treatment-related factors, including total delivered dose, target irradiated volume, deep location, concomitant chemotherapy etc. [6][7][8][9]. Differentiating PD from RN is of paramount importance because the treatment and management of these conditions are different.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At doses of 16-22 Gy given in a single fraction, RN may develop in up to 68 % of treated lesions, depending on several patient-related and treatment-related factors, including total delivered dose, target irradiated volume, deep location, concomitant chemotherapy etc. [6][7][8][9]. Differentiating PD from RN is of paramount importance because the treatment and management of these conditions are different.…”
Section: Discussionmentioning
confidence: 99%
“…Its efficacy, when used alone or in combination with whole-brain radiation therapy (WBRT), has been demonstrated in several randomized trials and multi-institutional studies that have shown a 12-month local control of 70 -90 % [2][3][4][5]. The most common complication of SRS is the development of brain radionecrosis (RN) that may occur in a significant proportion of irradiated lesions, especially when high single doses are delivered to large tumour volumes [6][7][8][9]. Differentiation of tumour progression (PD) from RN is challenging, as both conditions are characterized by similar neurological symptoms [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…First, the optimal timing of SRS and ipilimumab is unknown. Furthermore, given the possibility of pseudoprogression from both radiosurgery 68,69 and ipilimumab, 70 care must be taken when determining progression on surveillance imaging after the combination of SRS and ipilimumab.…”
Section: Ctla-4 Inhibition and Intracranial Radiosurgerymentioning
confidence: 99%
“…Elle apparaît classiquement 6 à 12 mois après la radiothérapie en conditions stéréotaxiques. Après radiochirurgie, environ 50 % des lésions apparaissent comme des radionécroses pures alors que les autres sont un mélange de cellules tumorales et de nécroses [28]. L'incidence varie de 2 à 22 % pour les radionécroses radiologiques et 1 à 14 % pour les symptomatiques [29,30].…”
Section: Radionécrose Après Radiothérapie En Conditions Stéréotaxiquesunclassified
“…Le volume ayant reç u une dose de 12 Gy (V12 Gy) en une séance semble prédictif à 1 an (risque : 0 % si V12 < 3,4 cm 3 , > 10 % si V12 Gy > 8,5 cm 3 ) [28]. Peu de données sont disponibles pour estimer précisément le risque de radionécrose un an après radiothérapie hypofractionnée en conditions stéréotaxiques.…”
Section: Après Une Séance Uniqueunclassified